A project management curriculum review through the interviews with project managers - Haron, Linariza (2018)
This paper presents a snapshot of the industry practitioners’ perspectives on project management practice, indicative from their expectations and reservations toward the discipline as a taught course. The data collection stage involved carrying out interviews with practicing project managers from public and private sectors. After the full transcripts of the interviews were completed and compiled, key themes were picked out and rearranged to reflect findings for project management knowledge and practice. At best, their narratives have determined that the essential modules for reading a project management degree must include general project management studies before specialization can take place. Some key subject areas are business acumen, leadership, communication, soft skills, managing people, budgetary and finance and the process areas. Next, when specializing in construction project management, this must be approached from the practice framework, giving a deeper treatment in the teaching of planning tools, in issues of initiation, procurement and procurement strategy, execution process and monitoring tools. And lastly, the course of study is substantiated with research dissertation exercise and project simulation. This framework potentially affirmed the rule that “trial and error” is no longer an option, particularly when graduate students are expected to undertake assignments in practice project management competently.